2017
DOI: 10.1017/s0954579417000074
|View full text |Cite
|
Sign up to set email alerts
|

Atypical dimensions of caregiver–adolescent interaction in an economically disadvantaged sample

Abstract: The Goal-corrected Partnership Adolescent Coding System (GPACS) has shown promise in assessing a secure as well as three atypical patterns of parent-adolescent interaction during a conflict discussion. The current study of 186 economically disadvantaged families examines the degree to which four GPACS patterns: Secure/Collaborative, Punitive, Role Confused and Disoriented—account for residual change in adolescents’ social competence and maladaptive behavior (internalizing, externalizing, and risk behaviors) be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 47 publications
(52 reference statements)
0
20
0
Order By: Relevance
“…For example, Poehlmann-Tynan et al’s (2017) study of child attachment in the context of parental incarceration shows clearly that the development of new observational procedures and coding systems is often a prerequisite to studying attachment in high-risk contexts given the extra-scientific constraints that bedevil scholars in this area. Likewise, two other papers contained in this Special Issue describe efforts to design or further validate assessments of the quality of adolescent–parent attachments via direct observations (Kobak et al, 2017; Martin, Sturge-Apple, et al, 2017). Such methodological contributions to the literature are timely and welcome.…”
Section: Methodological Insightsmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, Poehlmann-Tynan et al’s (2017) study of child attachment in the context of parental incarceration shows clearly that the development of new observational procedures and coding systems is often a prerequisite to studying attachment in high-risk contexts given the extra-scientific constraints that bedevil scholars in this area. Likewise, two other papers contained in this Special Issue describe efforts to design or further validate assessments of the quality of adolescent–parent attachments via direct observations (Kobak et al, 2017; Martin, Sturge-Apple, et al, 2017). Such methodological contributions to the literature are timely and welcome.…”
Section: Methodological Insightsmentioning
confidence: 99%
“…Judged against these goals for this Special Issue, we could not be more satisfied with the papers presented in this Special Issue, nor more grateful to the authors who contributed the studies reported herein. As the reader will no doubt recognize at a glance, the work contained in this Special Issue focuses on a notably wide range of contexts (e.g., institutional rearing; VanTieghem et al, 2017), conditions (e.g., poverty; Kobak, Zajac, Abbott, Zisk, & Bounoua, 2017), and caregiving behaviors (e.g., maltreatment; Roisman et al, 2017) likely to generate risk in relation to attachment-related individual differences, processes, and disruptions over development. In so doing, the papers presented here collectively not only (a) make significant contributions to advancing the basic science critical to acquiring a better understanding of the consequences of atypical caregiving for attachment-related outcomes but also (b) serve to further realize the translational promise of attachment theory and research to facilitate healthy development in at-risk populations via diverse attachment-related intervention efforts.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Adolescence is a critical time of transition from dependence on the family to more autonomous functioning in the community. This transition involves expansion of activities into a variety of new domains, including intimacy/ sexuality and work or career-related studies (e.g., Kobak, Zajac, Abbott, Zisk, & Bounoua, 2017). Notably, a variety of risky self-damaging behaviors are also initiated during adolescence (e.g., DuRant, Smith, Kreiter, & Krowchuk, 1999).…”
mentioning
confidence: 99%